2020
DOI: 10.22161/ijeab.54.37
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation: A way towards sustainable Agriculture

Abstract: Phytoremediation means utilizing the potential of a variety of plants to remediate soil, sludge, sediment and water (surface water and underground aquifers) contaminated with heavy metals at the point or non-point sources. Phytoremediation is solar energy-driven technology, eco-friendly and a cost-effective way of making soil and water pollutants free. It is a process of onsite remediation by using different biological processes of plants. Phytoremediation is known widely by different terms viz., green-remedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to results found in this study, it can be observed that the amaranthus hypochondriacus had higher Pb, Ni, and Zn levels than the sphagneticola trilobata. This difference in uptake could be explained by the fact that plants do not accumulate heavy metals in the same way, depending on their cellular and molecular constitution [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to results found in this study, it can be observed that the amaranthus hypochondriacus had higher Pb, Ni, and Zn levels than the sphagneticola trilobata. This difference in uptake could be explained by the fact that plants do not accumulate heavy metals in the same way, depending on their cellular and molecular constitution [23].…”
Section: Discussionmentioning
confidence: 99%
“…Plants have always been considered, in most cultures around the world, as a source of food and energy and for their therapeutic abilities [21,22]. For about two to three decades, researchers have developed a particular interest in a plant's capacity to store, degrade or mineralize certain polluting substances in the air, water, and soil [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heavy metal chromium finds extensive application in industrial processes including cement manufacturing, leather tanning, and metal plating. However, both persons and the ecosystem may be harmed by exposure to excessive chromium concentrations (Kerkeb & Kramer, 2003;Rai et al, 2019;Udawat & Singh, 2020). There are several methods for dealing with chromium contamination, such as phytotransformation, phytoextraction, and phytostabilization.…”
Section: Chromium Phytoremedia Onmentioning
confidence: 99%
“…These metal pollutants are made bioavailable for plants through root secretion of metal-chelating molecules into the surrounding rhizosphere [ 30 ], metal reductase in the plasma membrane, and proton extrusion from roots [ 26 ]. Several mechanisms of phytoremediation exist [ 2 , 9 , 31 , 32 ]. In phytoextraction, soil contaminants are taken up through the roots and accumulate in the shoots [ 33 , 34 ].…”
Section: Phytoremediationmentioning
confidence: 99%